2017
DOI: 10.5430/jnep.v7n9p107
|View full text |Cite
|
Sign up to set email alerts
|

Improving knowledge, skills, and attitudes of the nursing faculty members and postgraduate students towards plagiarism in academic writing

Abstract: Background and aim: Plagiarism is the use of concepts, words, manuscript and data without acknowledgment of the original source. It has become a worldwide problem, and a contentious matter in university education and research. The study aimed to improve knowledge, skills, and attitudes of the nursing faculty members and postgraduate students towards plagiarism in academic writing.Methods: A quasi-experimental (pre-post) design. Setting: The study was accomplished at the Nursing Faculty in Mansoura University. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Plagiarism may not always be deliberate and may result from students’ lack of knowledge about what constitutes plagiarism and/or how to properly quote published work (Dahl, 2007). Moreover, increased knowledge about plagiarism predicts an increased negative attitude towards plagiarism (Mansour et al, 2017). Plagiarism may result from students’ lack of confidence about how to avoid plagiarism (Macdonald and Carroll, 2006).…”
Section: Plagiarism and Student Engagementmentioning
confidence: 99%
“…Plagiarism may not always be deliberate and may result from students’ lack of knowledge about what constitutes plagiarism and/or how to properly quote published work (Dahl, 2007). Moreover, increased knowledge about plagiarism predicts an increased negative attitude towards plagiarism (Mansour et al, 2017). Plagiarism may result from students’ lack of confidence about how to avoid plagiarism (Macdonald and Carroll, 2006).…”
Section: Plagiarism and Student Engagementmentioning
confidence: 99%
“…The similar results were found in this study, the highly significant difference were found (p=<0.001) in all pre and post component of workshop, so the hands on workshop can contribution in faculty development program. [14][15] One of the study results highlight the 20% awareness of participant involved in research writing, the most common factor is the lack of time and the generalized acceptance of copy paste culture. [16][17] Another study results evidence the lacking of awareness about using software for plagiarism, and participants were not understand the basic dynamics that how to plagiarized the research work.…”
Section: Discussionmentioning
confidence: 96%
“…The combination of diverse educational backgrounds and experience levels has the potential to facilitate a wide range of research interests and methodologies. However, strategic initiatives may be necessary to enhance the research capabilities of the faculty members, such as providing opportunities for professional development, encouraging collaborations with researchers holding PhD degrees, and offering incentives for further education [ 22 ]. Regarding the faculty members' knowledge in various domains, it was observed that nearly two-thirds displayed proficiency in using and differentiating between software tools for citing scientific papers.…”
Section: Discussionmentioning
confidence: 99%